An Evaluation of Sexual Functions and Marital Adjustment in Female Patients with Fibromyalgia Syndrome - Davut Döner; Hatice Reşorlu; Coşkun Zateri; Başak Şahin; Hülya Ertekin; Sibel Oymak (Türk Osteoporoz Dergisi, 2019)

(untitled)
Objective:The purpose of this study was to investigate sexual functions and marital adjustment which are neglected issue in married female patients diagnosed with Fibromyalgia syndrome (FMS) and to reveal the factors affecting these.Materials and Methods:Sexually active, 47 married females who diagnosed with FMS and 50 healthy volunteers in a similar age group were included in the study. Beck anxiety inventory, beck depression inventory, female sexual function index (FSFI) and dyadic adjustment scale (DAS) evaluations were also performed for both groups. In the patient group, the severity of pain was evaluated by the visual analogue scale and functional impairment due to the disease was assessed by the fibromyalgia impact questionnaire (FIQ).Results:No significant difference was determined between the two groups in terms of socio-demographic features. FSFI and DAS total scores were significantly lower in the patient group compared to the controls (p<0.001, p=0.028, respectively). Low DAS scores were determined in patients with low FSFI scores (p=0.003, r=+0.043). Neither FSFI nor DAS scores have exhibited correlation with duration of disease and FIQ scores. Depression was correlated with both FSFI and DAS (p<0.001, r=-0.569; p<0.001, r=-0.546, respectively).Conclusion:In this study, sexual functions and marital adjustment were adversely affected in patients with FMS. This effect was found closely related to depression. However, there was no relationship determined between duration of the disease, the severity of pain and the functional impact.